Morphology and Molecular Phylogeny of Four Anaerobic Ciliates (Protista, Ciliophora, Armophorea), with Report of a New Species and a Unique Arrangement Pattern of Dikinetids in Family Metopidae - Song Li; Wenbao Zhuang; Xiaochen Feng; Alan Warren; Jun Gong (Microorganisms)
The diversity of anaerobic ciliates is greatly underestimated owing to the limitation in sampling and cultivation when compared with their aerobic counterparts. In this study, four anaerobic ciliates, viz. Brachonella abnormalis sp. nov., Brachonella contorta (Levander, 1894) Jankowski, 1964, Metopus contortus (Quennerstedt, 1867) Kahl, 1932, and Metopus major Kahl, 1932, were investigated by live observation, protargol staining and 18S rRNA gene sequencing. B. abnormalis sp. nov. can be separated from its congeners by a combination of the following features: bullet-shaped cell with a life size of about 130–190 × 90–120 μm, dikinetids distributed along dorsal dome kineties, highly developed adoral zone comprised of 87–107 polykinetids, making about 450° spiralization around the long axis. The present work demonstrates that two known species, M. contortus and M. major, have a special trait never previously reported, viz. short, regularly arranged preoral dome dikinetids. Species with short, regularly arranged dome dikinetids appear in divergent clades in SSU rRNA gene trees, which may infer that this trait evolved several times. Phylogenetic analyses based on SSU rRNA gene sequence data also support the monophyly of the genus Brachonella and the paraphyly of the order Metopida, respectively.